Adolescent pre‐treatment with oxytocin protects against adult methamphetamine‐seeking behavior in female rats. (17th November 2014) - Hicks, Callum; Cornish, Jennifer L.; Baracz, Sarah J.; Suraev, Anastasia; McGregor, Iain S.
Abstract: The neuropeptide oxytocin (OT), given acutely, reduces self‐administration of the psychostimulant drug methamphetamine (METH). Additionally, chronic OT administration to adolescent rats reduces levels of alcohol consumption in adulthood, suggesting developmental neuroplasticity in the OT system relevant to addiction‐related behaviors. Here, we examined whether OT exposure during adolescence might subsequently inhibit METH self‐administration in adulthood. Female Sprague‐Dawley rats were administered vehicle or OT (1 mg/kg, i.p.) once daily from postnatal days (PND) 28 to 37 (adolescence). At PND 62 (adulthood), rats were trained to self‐administer METH (intravenous, i.v.) in daily 2‐hour sessions for 10 days under a fixed ratio 1 (FR1) reinforcement schedule, followed by determination of dose‐response functions (0.01–0.3 mg/kg/infusion, i.v.) under both FR1 and progressive ratio (PR) schedules of reinforcement. Responding was then extinguished, and relapse to METH‐seeking behavior assessed following priming doses of non‐contingent METH (0.1–1 mg/kg, i.p.). Finally, plasma was collected to determine pre‐treatment effects on OT and corticosterone levels. Results showed that OT pre‐treatment did not significantly inhibit the acquisition of METH self‐administration or FR1 responding. However, rats pre‐treated with OT responded significantly less for METH under a PR reinforcement schedule, and showed reduced METH‐primed reinstatement with the 1 mg/kg prime. Plasma OT levels were also significantly higher in OT pre‐treated rats. These results confirm earlier observations that adolescent OT exposure can subtly, yet significantly, inhibit addiction‐relevant behaviors in adulthood. Abstract : This study examined whether oxytocin (OT) exposure during adolescence inhibits methamphetamine (METH) self‐administration in adulthood in female Sprague‐Dawley rats. Results showed that OT pretreatment (1 mg/kg, i.p.; 10 injections) did not inhibit the acquisition of METH self‐administration (i.v.) or fixed‐ratio 1 responding. However, OT pretreated rats responded less for METH under a progressive ratio schedule and showed reduced METH‐primed reinstatement, as well as increased plasma OT levels. Adolescent OT exposure may therefore subtly, yet significantly, inhibit addiction‐relevant behaviors in adulthood.